2022
DOI: 10.1038/s41598-022-17542-z
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal microbiota profiling of pregnant women with SARS-CoV-2 infection

Abstract: We aimed to analyze the nasopharyngeal microbiota profiles in pregnant women with and without SARS-CoV-2 infection, considered a vulnerable population during COVID-19 pandemic. Pregnant women were enrolled from a multicenter prospective population-based cohort during the first SARS-CoV-2 wave in Spain (March-June 2020 in Barcelona, Spain) in which the status of SARS-CoV-2 infection was determined by nasopharyngeal RT–PCR and antibodies in peripheral blood. Women were randomly selected for this cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 48 publications
10
14
0
Order By: Relevance
“…In the MRS+ samples, members of the Bifidobacteriaceae and Oscillospiraceae families were enriched, while Microbacteriaceae was decreased with a significant difference, suggesting an alteration in the intestinal microbiota due to the presence of the SARS-CoV-2 virus in infected pregnant women. A previous study of nasopharyngeal swab samples taken from Spanish pregnant women with COVID-19 reported a bacterial diversity at the phylum level similar to that in our work, where the Prevotellacea family had the highest abundance [ 31 ]. In another comparative study in the Italian population carried out using rectal swab samples from healthy individuals versus COVID-19 patients at different phases of the disease, the comparison of the microbial composition pointed out significant changes in the bacterial communities during progressive phases of the disease [ 29 ].…”
Section: Discussionsupporting
confidence: 84%
“…In the MRS+ samples, members of the Bifidobacteriaceae and Oscillospiraceae families were enriched, while Microbacteriaceae was decreased with a significant difference, suggesting an alteration in the intestinal microbiota due to the presence of the SARS-CoV-2 virus in infected pregnant women. A previous study of nasopharyngeal swab samples taken from Spanish pregnant women with COVID-19 reported a bacterial diversity at the phylum level similar to that in our work, where the Prevotellacea family had the highest abundance [ 31 ]. In another comparative study in the Italian population carried out using rectal swab samples from healthy individuals versus COVID-19 patients at different phases of the disease, the comparison of the microbial composition pointed out significant changes in the bacterial communities during progressive phases of the disease [ 29 ].…”
Section: Discussionsupporting
confidence: 84%
“…Irrespective of COVID-19 disease status, the nasopharyngeal microbiota of the symptomatic patients, i.e., Irrespective of the disease status, the nasopharyngeal microbiota in Indian samples was found to be dominated by the phylum Firmicutes, Proteobacteria, and Actinobacteriota and the family Staphylococcaceae and Corynebacteriaceae. This is in line with the reports presented in earlier studies inspecting nasopharyngeal microbiota in other geographies [27], [28], [29].…”
Section: Association Of Inferred Functions With Microbiota Samples Du...supporting
confidence: 93%
“…[27], [23] barring a few exceptions [29]. Our findings also indicate a lower diversity associated with COVID-19, concurring with these findings.…”
Section: Association Of Inferred Functions With Microbiota Samples Du...supporting
confidence: 91%
“…A recent study from Spain reported that the overall composition of the nasopharyngeal microbiota differs in pregnant women with SARS-CoV-2 infection compared to healthy controls ( 37 ). Specifically, the authors observed a higher abundance of Prevotellaceae family (Bacteroidales order) in pregnant women with active SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies exploring the impact of SARS-CoV-2 infection on the microbiota have focused on the lung (32), gut (33)(34)(35), and nasopharyngeal mucosa (36) in non-pregnant adults. Two studies to our knowledge, have characterized the gut and nasopharyngeal microbiotas at the time of delivery and post-partum colostrum of pregnant women with SARS-CoV-2 infection (37,38). The first study conducted in Spain, reports an increased abundance of Bacteroidales in the nasopharyngeal swabs of pregnant women with active SARS-CoV-2 infection compared to healthy controls.…”
Section: Introductionmentioning
confidence: 99%